La lectura de la obra de Camus en España : elementos para una teoría de la lectura del texto extranjero - Cruces Colado, Susana (1998)
"From the theoretical perspective of the polysystems, we have started from the premise according to which the literature that is written in a country does not remain isolated, but is connected with other literatures. The result of these contacts crystallizes in the introduction of texts which were originally written for another culture, normally thorough translations. Besides, the imported text is the subject of discourse of mediation which introduces, places it in the literary system, and ascribes it a meaning which will accepted as the adequate one for a society, and which finds itself assigned to a public made up of readers who are not necessarily specialists in literature. The translation as well as the discourse of mediation or accompaniment are reading activities, which have been carried out from the values, the background, the knowledge and the predominant ideological lines of literature, and, consequently from the target culture, therefore this reading has to be necessarily different from the exported culture. To prove this thesis, we have carried out study of Camus work during the historic Franco's dictatorship (1936-1975) and both the aesthetic and ideological determinants it was subjected to. In order to do this, we have to resort to translations and a corpus of texts which were published commenting, criticizing this work and constructing a image about Camus. This has allowed us to determine the history of the translations, the role of censorship played in the diffusion and reception of his work, as well as the aesthetic and ideological values which guided said reading, and the evolution of the same during the Franco Era."